Sol-Gel Derived Mg-Based Ceramic Scaffolds Doped with Zinc or Copper Ions: Preliminary Results on Their Synthesis, Characterization, and Biocompatibility - Georgios S. Theodorou; Eleana Kontonasaki; Anna Theocharidou; Athina Bakopoulou; Maria Bousnaki; Christina Hadjichristou; Eleni Papachristou; Lambrini Papadopoulou; Nikolaos A. Kantiranis; Konstantinos Chrissafis; Konstantinos M. Paraskevopoulos; Petros T. Koidis (International Journal of Biomaterials)
Glass-ceramic scaffolds containing Mg have shown recently the potential to enhance the proliferation, differentiation, and biomineralization of stem cells in vitro, property that makes them promising candidates for dental tissue regeneration. An additional property of a scaffold aimed at dental tissue regeneration is to protect the regeneration process against oral bacteria penetration. In this respect, novel bioactive scaffolds containing Mg2+ and Cu2+ or Zn2+, ions known for their antimicrobial properties, were synthesized by the foam replica technique and tested regarding their bioactive response in SBF, mechanical properties, degradation, and porosity. Finally their ability to support the attachment and long-term proliferation of Dental Pulp Stem Cells (DPSCs) was also evaluated. The results showed that conversely to their bioactive response in SBF solution, Zn-doped scaffolds proved to respond adequately regarding their mechanical strength and to be efficient regarding their biological response, in comparison to Cu-doped scaffolds, which makes them promising candidates for targeted dental stem cell odontogenic differentiation and calcified dental tissue engineering.